Collaborative crowd games exploring participatory sensing and intelligent artificial life simulation techniques - Martins, Gustavo (2022)
Communication, work, and recreation, mobile devices have become an integral component of modern life. The goal of this study was to figure out how these devices might be used to boost the experience at entertainment events. For this, we created Cabo DIGuerra, a collaborative game that uses motion and audio sensors in an interactive dynamic with the public, based on the concepts of Mobile Crowd Sensing and User Experience, and from which a more advanced version, the Bumbometer, was used in two major events in Brazil's northern region. Furthermore, a prototype of an application was created that combined the artificial life system based on boids, the Bumboids.